The Efficiency of Activating the MasR/Ang 1-7 Pathway to Reduce Muscle Atrophy and Functional Loss Following Denervation - Albadrani, Hind (Université d'Ottawa / University of Ottawa, 2021)
Denervation leads to skeletal muscle atrophy, which is a decrease in muscle mass and force; the latter exceeding expectation from mass loss. In some cases, nerve regeneration following an injury takes several months. During this time, muscle mass and force loss become severe as fibers are replaced by connective and fat tissue, which can further prolongs normal muscle function recovery once reinnervation occurs. The objectives of this study were 1) document the angiotensin 1-7 (Ang 1-7) hypertrophic effect in innervated mouse skeletal muscle; 2) test the hypothesis that Ang 1-7 prevents muscle atrophy and maintain force following short 2 and 4 week denervation; 3) as well as following long 16 week denervation. Innervated and denervated mice were treated with Ang 1-7 or diminazene aceturate (DIZE), an ACE2 activator, to increase plasma Ang 1-7 level. In normal innervated extensor digitorum longus (EDL) and soleus muscle, Ang 1-7 increased muscle weight, cross sectional area (CSA) and tetanic force, which represents the muscle maximum force. During the short denervation period (2-4 weeks), Ang 1-7 did not prevent muscle mass and CSA loss, but fully abolished the loss of normalized tetanic force to CSA while accentuating twitch force. Normalized tetanic force was maintained as Ang 1-7 partially reduced the extent of membrane depolarization which normally observed with denervation, and it fully prevented the loss of membrane excitability. The protective effect of Ang 1-7 on maximum tetanic force was also observed after 16 weeks of denervation, but only in EDL not in soleus. About 35-40% of denervated EDL and soleus muscle fibers became reinnervated over the 16 week period and Ang 1-7 enhanced the recovery of muscle mass and tetanic force in both EDL and soleus. All Ang 1-7 effects on twitch and tetanic force were completely blocked by A779, a Mas receptor (MasR) antagonist, and were not observed in MasR deficient (MasR / ) muscles. Ang 1-7 did not affect how denervation modulates changes in the protein content MuRF-1 atrogin-1, two atrophic proteins, total and phosphorylated Akt, S6K and 4EPB, three hypertrophic proteins. So, the Ang 1-7 effect involves an activation of its MasR, but it is not clear which intracellular pathway it then affects. This is the first study providing evidence that Ang 1-7 maintains normal muscle function in terms of tetanic force and membrane excitability during 2, 4 and 16 week denervation periods.
Keywords: Denervation; Muscle Atrophy; Ang 1-7; MasR; Membrane Excitability; Tetanic Force; Hypertrophy; Atrophy